Penghargaan Hak Berpendapat Anak di Pengadilan: Studi Kasus di Pengadilan Negeri Semarang - Rika Saraswati; V Hadiyono (Sawwa: Jurnal Studi Gender, 2018)
The right of children to be heard are guaranteed by the Child Protection Act in Indonesia. This is very principle as the main factor for judges to make decisions regarding disputes over child custody. The purpose of this study is to examine the implementation of laws in Indonesia that regulate children's rights to be heard in court. Data was taken by conducting documentary research and field research by collecting several decisions from the District Court of Semarang and interviewing the judges who handled this matter. This research shows that children are rarely asked for their opinions in the courtroom; Their opinions are only considered information, not as witness statements. As a result, their opinions and expectations have no effect on court decisions. The study also shows that the law in Indonesia has regulated the obligation of judges to listen to the opinions of children in court, but judges never consider it.